UMP organised IPT Mandarin Speaking Competition 2012 - UMP, PNC
Universiti Malaysia Pahang (UMP) organised the IPT Mandarin Speaking Competition 2012 which was aimed at enhancing communication skills among undergraduates in institutes of higher learning nationwide.